An evaluation of the curriculum of higher Islamic Education in Bangladesh : a case study - Ullah, Mohammad Nayamat (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This study attempts to evaluate and review the curriculum of higher Islamic education in Bangladesh in order to discover its merits and demerits. It analyses and assesses the curriculum to examine whether it is comprehensive, integrated and holistic, and whether it is sufficient to meet the needs of the present time. The researcher employs a combination approach of research methods, namely historical, philosophical analysis, and curriculum criticism. The curricula of two selected programmes were examined; Fazil (three-year bachelor) of madaris affiliated to Islamic University Kushtia Bangladesh and Bachelor of Arts (four-year honours) in Islamic Studies at colleges affiliated to the National University Bangladesh. This research is conducted on the basis of the philosophical foundation and conceptual framework of higher Islamic education curriculum which comprises of four dimensions: faith (Iman), knowledge (Ilm), action ('Amal), ethics and morality (Akhlaq). The framework has been developed based on three curriculum models of Al-Attas, Rosnani and the International Islamic University Malaysia (IIUM). The critical analysis discovers some inconsistencies and demerits of the existing curriculum; mainly that the educational philosophy, aims, and objectives are not clearly outlined, and that the contents and pedagogy are not conducive for the overall development of the graduates. The present study proposes a balanced and sound philosophy, comprehensive objectives and aims of higher Islamic education in Bangladesh, conforming to the recommendations of the World Conferences on Muslim Education, the thoughts of renowned Muslim scholars and the national ideology of the country, which is enshrined in the Basic Constitution. The research concludes that due to the changing circumstances at home and abroad, social demands and emerging technologies, a thorough reform of the curriculum is crucial. Finally, the research offers some necessary guidelines on forming holistic, comprehensive and integrated curricula comprising of Revealed Knowledge, and Natural and Social Sciences.